Fish you were here - Venable, Colleen A. F. (Venable, Colleen A. F. Guinea PIG, pet shop private eye, 2011)
Guinea pig Sasspants knows something is wrong with ninth-grader Viola, the new pet shop assistant, so when Mr. Venezi goes missing Sasspants and Hamisher put their private investigation skills to the test.